STUDENTS’NEEDS ANALYSIS IN THECONTENT OF VOCATIONAL HIGH SCHOOL ENGLISH TEXTBOOK - Sri Supiah Cahyati (DIDAKTIK, 2014)
Learning English in Vocational High School (SMK) is different from that in Senior High School. In SMK, the orientation is to prepare students to be able to take part in the business & industry work. Consequently, English teachers in vocational school are expected to have the ability to analyze the needs of the students so that they can design an appropriate teaching-learning process. The aim of this study was to identify some factual information about the needs of vocational students in learning English, especially in the English-language skills (Listening, Speaking, Reading, and Writing) and some of language components in English (Grammar & Vocabulary), and to analyze the appropriacy between the content of English textbooks with the vocational students’ needs. The subjects in this study were the vocational school teachers and English textbooks of 7 (seven) SMK which has the TKJ department in Bandung and Cimahi. The results showed that the needs of students towards learning English is to meet the academic professions and the future needs of the students, which involved the skills of the language and some of the language components. Whereas in the case of appropriacy between the content of the English textbooks and the vocational students’ needs, it was found that the English textbooks was more focused on describing the English language competences in general and not specifically focused on the Department of TKJ itself.